2023
DOI: 10.1044/2022_ajslp-22-00232
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Training Needs in Pediatric Feeding for Allied Health Professionals: An Australian Perspective

Abstract: Purpose: Clinician experience and confidence can negatively impact pediatric feeding service availability, but limited research has investigated what training allied health professionals (AHPs) need to increase these factors. This study developed and distributed a survey investigating Australian AHPs' self-reported confidence and anxiousness, training needs, factors impacting training access, and training preferences. Method: This study was conducted ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The escalating prevalence of PFD [13] has resulted in an increased requirement for clinical skills in this area. Unfortunately, many clinicians report low confidence and readiness to practice [14][15][16] and expertise is often held at tertiary care centers. Access to training is described as an issue in pediatric feeding care, with time, distance, and travel requirements cited as barriers [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The escalating prevalence of PFD [13] has resulted in an increased requirement for clinical skills in this area. Unfortunately, many clinicians report low confidence and readiness to practice [14][15][16] and expertise is often held at tertiary care centers. Access to training is described as an issue in pediatric feeding care, with time, distance, and travel requirements cited as barriers [16].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, many clinicians report low confidence and readiness to practice [14][15][16] and expertise is often held at tertiary care centers. Access to training is described as an issue in pediatric feeding care, with time, distance, and travel requirements cited as barriers [16]. A recent Australian survey of training needs found that providing opportunities in an online format was a commonly reported facilitator to increasing access to training, with infant feeding identified as a priority area [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation